Epididymo-Orchitis: A Rare Manifestation of Tuberculosis Infection - Pattiselanno, Yoshua Ariel; Pattiselanno, Laurenz Lolly; Leo, Benedreky; Hadi, Choirul; Angel, Sharon Hanmy (Jurnal Respirasi, 2024)
Introduction: Tuberculosis (TB) is caused by Mycobacterium tuberculosis (MTB) and now represents a significant global health concern, with an estimated 10 million people infected with TB in 2022, equivalent to 133 incident cases per 100,000 population. Indonesia faces a substantial burden. The World Health Organization (WHO) estimates 969,000 TB cases, with 717,941 confirmed cases reported. Extrapulmonary TB, contributing to 15% of TB cases, affects various areas such as bones, pleura, lymph nodes, genitourinary system, peritoneum, and meninges. Tuberculous epididymo-orchitis, a rare type of extrapulmonary TB, is characterized by MTB infection in the epididymis or testis. Case: A 31-year-old male was presented to the Emergency Department of Budi Rahayu General Hospital, Pekalongan, with a fever, bitter taste, body aches, and cough. Initially hospitalized for five days and discharged upon improvement of symptoms, the patient returned with fatigue, cough, and black stools. After being admitted under internist and pulmonary specialist care due to a suspected left lung TB apical lesion, biomolecular testing (GeneXpert) was performed. Consultation with a urologist revealed scrotal pain, prompting further tests including urine acid-fast bacilli (AFB) examination, testicular ultrasound, and aspiration culture. The patient was diagnosed with TB epididymo-orchitis and treated with a Category 1 TB regimen. Conclusion: TB epididymo-orchitis is a rare case requiring thorough diagnostic evaluation encompassing anamnesis, physical examination, and diagnostic procedures. Early detection and appropriate management are vital in combating this challenging disease.